ТHE BEGINNING OF THE WORLD ACCORDING TO HESIODS AS THE BIRTH OF PHILOSOPHICAL ONTOLOGY - Ігор ПАВЛЕНКО (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The work of Hesiod, an ancient Greek epic poet, is considered, in particular, his poem “Theogony”, as one of the first cosmogonic constructions in European culture. Particular attention is drawn to the image and concept of Chaos – the initial state of the world, which also has a creative, creative essence. The primary instances that appear together with Chaos – Gaia, Tartarus and Eros also act as elements of the basic ontological model. The attitude of the ancient philosophical tradition to the concept of Chaos, which was problematized even by the pre-Socratics and compared with the famous Orphic cosmologies, is analyzed. In this sense, the image of Chaos in Hesiod can be considered as the first principle of building the world by analogy with the search for arché in later philosophers, as well as in its abstract, idealized form – the initial theoretical model of being and the beginning of ancient ontology. Of particular interest in this sense is Chaos, a rather complex and mysterious reality that is primary in relation to others and, moreover, is itself a creative force. The problem can be formulated as follows: can Chaos in Hesiod’s poem be considered a mythological-poetic ontology, an analogue and prerequisite of the philosophical concept of being, or even a certain essence of the world, its eternal integral part. The task of the study is to describe a general approach to understanding Chaos in Hesiod’s poem as an ontological essential first principle, which serves as a prototype of the philosophical ontology of later philosophers. Chaos can be interpreted as the original state of being and as a reference system for all world coordinates and the ideal beginning of the world. The original, initial state of the world, as well as the origin of the latter, is a cross-cutting theme of ancient Greek philosophy and science. Already in the early theogony, in the Orphics and in Hesiod, we find a certain mythological-poetic and, at the same time, religious-philosophical model of the origin of the world and its first elements. It would be too bold to consider these rather fantastic images and constructions as a real philosophical or scientific theory, which already in the understanding of the ancient Greeks should have had clearly defined principles and a consistent logical structure. Nevertheless, already in the first attempts to describe the structure of the universe we see an attempt to find the beginning from which a kind of ontological intuition of ancient Greek philosophy begins and which will later lead to the emergence of the main philosophical schools. Moreover, this intuition allowed us to pose a question that is still the basis of ontological problems. Even a preliminary consideration of the historical-philosophical material demonstrates the possibility of various interpretations of the ontological constructions of early ancient cosmogonies. The vision of Chaos in Hesiod proposed here is the first step towards a hermeneutic reconstruction of the primary foundations of ancient Greek philosophy and its mythological and poetic origins.